Efficiency of micro finance institutions and financial Sustainability in Jaffna District - Balagobei, S. (IISTE, 2016)
Microfinance institutions (MFIs) provide a range of financial services to poor people. This study aims to identify the relationship between efficiency and financial sustainability of microfinance institutions in Jaffna district. For the purpose of this study, Co-operative Rural Banks under two MPCS were selected by using the convenience sampling method. Data was collected and analyzed by using the SPSS for the period of 2007-2009. In this study, correlation and regression analysis were used. The results show that administrative efficiency and operating efficiency are strongly positive associated with financial sustainability among co-operative Rural Banks in Jaffna district. Further the study reveals that administrative efficiency and operating efficiency have a significant impact on financial sustainability.
Keywords: Microfinance institutions; Administrative efficiency; Operating efficiency; Financial sustainability